Antifungal In Vitro Activity of Pilosulin- and Ponericin-Like Peptides from the Giant Ant Dinoponera quadriceps and Synergistic Effects with Antimycotic Drugs - Hilania Valéria Dodou Lima; Carolina Sidrim de Paula Cavalcante; Gandhi Rádis-Baptista (MDPI AG, 2020)
Venoms from ants comprise a rich source of bioactive peptides, including antimicrobial peptides. From the proteome and peptidome of the giant ant Dinoponera quadriceps venom, members of five known classes of antimicrobial peptides were disclosed (e.g., dermaseptin-, defensin-, ICK-, pilosulin- and ponericin-like types). Based on comparative analysis, these family members have structural determinants that indicate they could display antimicrobial activities. In previous works, pilosulin- and ponericin-like peptides were demonstrated to be active against bacteria, fungi, and parasites. Herein, the antifungal activity of ponericin- and pilosulin-like peptides were assessed, aiming at the expansion of the knowledge about AMPs in predatory ants and the development of new microbicide strategies to deal with difficult-to-treat fungal infections. Synthetic pilosulin- (Dq-2562, Dq-1503, and Dq-1319) and ponericin-like (Dq-3162) peptides were evaluated for their fungicide and fungistatic activities against different species of Candida, including a drug-resistant clinical strain. The MICs and MLCs were determined for all peptides individually and in combination with general antifungal drugs by the microdilution method. The time-kill kinetic curves were set up by means of a luminescent reagent, of which the light signal is proportional to the number of viable cells. The candicidal synergism observed by the combination of subinhibitory concentrations of peptides and general antimycotic drugs were quantified by the checkerboard test and fluorescent dye permeation assay. The influence of ergosterol on the antifungal activity was verified by supplementation of culture medium. The pilosulin- (Dq-2562 and Dq-1503) and ponericin-like (Dq-3162) were the most active peptides, displaying a broad spectrum of antifungal activity in vitro, with MICs in the range of 0.625 to 10 µM. The combination of peptides and conventional antimycotic drugs displayed a synergistic reduction in the MIC values of individual peptides and drugs, while soluble ergosterol in the culture medium increased the MICs. The fungicide and fungistatic activity of the individual peptides and peptides in combination with antimycotics were time-dependent with a rapid onset of action and long-lasting effect, which involved membrane disruption as an underlying mechanism of their action. Altogether, pilosulin- and ponericin-like peptides from the giant ant D. quadriceps venom display a broad-spectrum of candicidal activity, what allows their inclusion in the row of the antifungal peptides and gives support for further studies on the development of strategies to fight candidiasis.